Gut microbiota and postoperative complications in colorectal surgery and its potential association with intestinal permeability and NLRP6 inflammasome - Buitrago-Ruiz, Manuel; Arias-Sánchez, Celia; Asensio-López, Maria Magdalena; Martínez-García, Juan José; Soria-Aledo, Victoriano; Valero-Navarro, Graciela; Cuevas, Santiago (Frontiers in Immunology, 2026)
This manuscript reviews the current evidence describing the relationships between surgical trauma, altered intestinal permeability, dysbiosis, inflammasome activation, and postoperative inflammation in the development of AL. Surgical tissue disruption and anastomosis creation can modify the intestinal microbiota and compromise epithelial barrier function, promoting a proinflammatory environment mediated by inflammasomes such as NLRP3, NLRC4, and NLRP6. This review analyses the inflammatory pathways that may regulate intestinal homeostasis, their potential contribution to postoperative complications such as AL, and how these insights may guide future preventive strategies or help identify patients at increased risk.